Understanding Factors That Predict Advance Directive Completion - Siobhan P. Aaron; Christine Musacchio; Sara L. Douglas (Palliative Medicine Reports, 2022)
Background: Advance care planning was designed for the purpose of ensuring that patients receive care at end of life (EOL) that is congruent with their wishes, goals, and values. Despite the evidence of the negative impact of not having advance directives (ADs), only one-third of adults in the United States have written ADs. Determining the patient's goals of care in the setting of metastatic cancer is vital to the delivery of high-quality healthcare. Although much is known about barriers to AD completion (e.g., the uncertainty of the disease process and trajectory, readiness of patient and family to have these discussions, and patient?provider communication barriers), little is known about the role of both patient and caregiver factors influencing AD completion. Objective: This study aimed to understand the relationship between patient and family caregiver demographic characteristics, and processes, and their influence on AD completion. Design: This study was a cross-sectional descriptive correlational design and employed secondary data analysis. The sample was composed of 235 patients with metastatic cancer and their caregivers. Results: A logistic regression analysis was performed to analyze the relationship between predictor variables and the criterion variable of AD completion. Out of the 12 predictor variables, only 2 variables (patient age and race) predicted AD completion. Of those two predictor variables, patient age made a greater and unique contribution to explaining AD completion, compared with patient race. Conclusion: There is a need for further research on cancer patients with historical low AD completion.